2021
DOI: 10.1073/pnas.2023265118
|View full text |Cite
|
Sign up to set email alerts
|

Early fMRI responses to somatosensory and optogenetic stimulation reflect neural information flow

Abstract: Blood oxygenation level–dependent (BOLD) functional magnetic resonance imaging (fMRI) has been widely used to localize brain functions. To further advance understanding of brain functions, it is critical to understand the direction of information flow, such as thalamocortical versus corticothalamic projections. For this work, we performed ultrahigh spatiotemporal resolution fMRI at 15.2 T of the mouse somatosensory network during forepaw somatosensory stimulation and optogenetic stimulation of the primary moto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(71 citation statements)
references
References 83 publications
(110 reference statements)
6
65
0
Order By: Relevance
“…For example, we found a factor of 3 higher displacement when activating one central layer instead of layer 1. As neuronal activity is usually distributed across several layers in most fMRI paradigms, the activated tissue volume will probably be even higher while the highly vascularized and perfused central layers are expected to dominate local tissue displacement effects ( Shen et al, 2008 ; Jung et al, 2021 ). We found that the relative displacement effect (normalized by the volume of the activated layer segment) slightly decreases from outer to inner layers.…”
Section: Discussionmentioning
confidence: 99%
“…For example, we found a factor of 3 higher displacement when activating one central layer instead of layer 1. As neuronal activity is usually distributed across several layers in most fMRI paradigms, the activated tissue volume will probably be even higher while the highly vascularized and perfused central layers are expected to dominate local tissue displacement effects ( Shen et al, 2008 ; Jung et al, 2021 ). We found that the relative displacement effect (normalized by the volume of the activated layer segment) slightly decreases from outer to inner layers.…”
Section: Discussionmentioning
confidence: 99%
“…To calculate group-averaged fMRI maps, a study-specific mouse brain template was constructed from CBV-weighted fMRI images based on a previously used pipeline (45, 46), as follows. First, the brain area was semiautomatically extracted from the temporal average of all fMRI images for each animal, and intensity nonuniformity was corrected with bias field estimation.…”
Section: Methodsmentioning
confidence: 99%
“…The fMRI response maps for individual animals were generated using preprocessing and general linear model (GLM) analysis. The steps of preprocessing were previously described in detail (30, 45). In short, preprocessing included slice timing correction, image realignment for minor head motions, linear signal detrending for signal drift removal, and time course normalization by the average of the baseline period.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Being able to use high spatiotemporal resolution is also critical to discern the direction of information flow using the onset times of fMRI responses. For example, Jung and colleagues [ 72 ] applied a GRE-EPI sequence at an ultra-high magnetic field (15.2 T) with a temporal resolution of 250 ms and spatial resolution of 156 × 156 × 500 μm 3 during either electrical paw stimulation or optogenetics stimulation of the motor cortex. Their results showed that the order of onset times varies between regions and active layers and coincides with their known sequence of neural activation.…”
Section: Introductionmentioning
confidence: 99%